BIOSINTESIS NANOPARTIKEL PERAK EKSTRAK ETANOL 96% DAUN KELOR (Moringa oleifera) DAN UJI AKTIVITASNYA SEBAGAI ANTIOKSIDAN - Fujiana Abd Karim; Robert Tungadi; Nur Ain Thomas (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Moringa leaf potentially has a high antioxidant becouse it contains secondary metabolite, one of which is quercetin. Therefore, to avoid harmful chemicals in the synthesis of silver nanoparticles, it is made by using a bio reductant of Moringa leaf extract. This study aims to know the optimal temperature in the formation of silver nanoparticles, to characterize the nanoparticle, and to rest the antioxidant AgNPs of Moringa leaf by using the DPPH method. This is a laboratory experimental study. The synthesis of nanoparticles uses a concentration of 0,4% Moringa leaf extract, which is reacted to AgNO3 with a concentration of 1 mM in a ratio of 1:9 at various temperatures of 60oC, 70oC, and 80oC for 30 minutes. The formed nanoparticles are characterized by using UV-VIS spectrophotometry and showing the optimum temperature for nanoparticles formation, which is 80oC. It is then continued to characterize using PSA and showing the average size of nanoparticles at a temperature of 80oC, which is 82,9 nm with a PDI value of 0,225. The result of the calculation of IC50 AgNPs shows that Moringa leaf obtains a value of 61.78 ppm, which is included in the strong category, meanwhile the thick extract of Moringa leaf without the addition of silver nanoparticles obtain a value of 124.41 ppm, which is included in the weak category.